The Causes of China's Great Famine, 1959-1961: County-Level Evidence - Hiroyuki Kasahara; Bingjing Li (Center for Economic Studies and ifo Institute (CESifo), 2017)
This study provides evidence that the over-export of grains aggravated the severity of China's Great Famine. We collect county-level data for the 1953-1965 period on death rates, birth rates, amounts of grain procured, output of different types of grain, crop productivity, weather conditions, distance to railways, and the number of Chinese Communist Party (CCP) members. We exploit county-level variations in the types of crops each county specialized in to construct Bartik-style measures of export shocks. We regress the death rates on the Bartik export measures and use the weather shocks as instruments for measuring output and consumption. The regression results suggest that increases in grain exports substantially increase death rates, and the effect of grain exports on death rates is larger in counties with lower current output, higher two-period lagged output, larger distance to railways, and a smaller percentage of local CCP members. We also estimate the effects of the procurement policy, examine the relationship between the death rates and the average level of consumption at the county-level during the famine period, and conduct counterfactual experiments to quantify the relative importance of different causes of the Great Famine. The counterfactual experiments indicate that the effect of grain exports explains 12 percent of the excess deaths, which amounts to 1/5 of the effect of the increase in procurement rates between 1957 and 1959. By comparing the distribution of county-level counterfactual changes in death rates if the amount of grain exports in 1959 had been the same as that in 1957, we find that the distribution of the high-export-exposure counties first-order stochastically dominates that of the low-export-exposure counties.
Keywords: F14; 330; famine; over-export of grains; inflexible procurement; Great Leap Forward